Contact lenses coated with hybrid multifunctional ternary nanocoatings (Phytomolecule-coated ZnO nanoparticles:Gallic Acid:Tobramycin) for the treatment of bacterial and fungal keratitis. (1st July 2021) - Khan, Shakeel Ahmad; Shahid, Sammia; Mahmood, Tahir; Lee, Chun-Sing
Abstract: Contact lenses are widely used for visual corrections. However, while wearing contact lenses, eyes typically face discomforts (itching, irritation, burning, etc.) due to foreign object sensation, lack of oxygen permeability, and tear film disruption as opposed to a lack of wetting agents. Eyes are also prone to ocular infections such as bacterial keratitis (BK) and fungal keratitis (FK) and inflammatory events such as contact lens-related acute red eye (CLARE), contact lens peripheral ulcer (CLPU), and infiltrative keratitis (IK) caused by pathogenic bacterial and fungal strains that contaminate contact lenses. Therefore, a good design of contact lenses should adequately address the need for wetting, the supply of antioxidants, and antifouling and antimicrobial efficacy. Here, we developed multifunctional gallic acid (GA), phytomolecules-coated zinc oxide nanoparticles (ZN), and phytomolecules-coated zinc oxide nanoparticles + gallic acid + tobramycin (ZGT)-coated contact lenses using a sonochemical technique. The coated contact lenses exhibited significant antibacterial (>log10 5.60), antifungal, and antibiofilm performance against BK-causing multidrug resistant bacteria ( Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia. coli ) and FK-related pathogenic fungal strains ( Candida albicans, Aspergillus fumigatus, and Fusarium solani ). The gallic acid, tobramycin, and phytomolecules-coated zinc oxide nanoparticles have different functionalities (-OH, -NH2, -COOH, -COH, etc.) that enhanced wettability of the coated contact lenses as compared to that of uncoated ones and further enabled them to exhibit remarkable antifouling property by prohibiting adhesion of platelets and proteins. The coated contact lenses also showed significant antioxidant activity by scavenging DPPH and good cytocompatibility to human corneal epithelial cells and keratinocytes cell lines. Statement of significance: Multifunctional coated lenses were developed with an efficient sonochemical approach. Lens surface was modified with nanocoatings of ZnO nanoparticles, gallic acid, and tobramycin. This synergistic combination endowed the lenses with remarkable antimicrobial activity. Coated lenses also showed noteworthy antifouling and biofilm inhibition activities. Coated lenses showed good antioxidant, biocompatibility, and wettability characteristics. Graphical abstract: Image, graphical abstract